Struggle for Russia : Power and Change in the Democratic Revolution. - Khasbulatov, R. I. (Ruslan Imranovich) (Routledge, 1993)
A man who has been one of the new Russia's most influential politicians presents his unique perspective on past and future in Russia politics, the events of August 1991 and his own part in resisting the attempted coup.